Contextual Content of Friday Sermons in the Religious Moderation Discourse in Jayapura City - Syarifuddin, Syarifuddin; Abubakar, Asnandar; Hamsiati, Hamsiati; Hamid, Wardiah (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
The study of Friday sermon content is always interesting to discuss, especially in Muslim minority areas. This study describes the content of the Friday sermons selected by the preachers in Jayapura City. The research method used is a qualitative method by recording Friday sermons from several types of mosques, namely the Great Ash Shalihin Mosque in Jayapura City, the Baiturrahim Mosque, Kotaraja, Skyland Complex, and the IAIN Fathul Muluku Jayapura Campus Mosque. This study found that the procedure for selecting khatibs in Jayapura City was coordinated by the Ministry of Religious Affairs except for Heram and Muara Tami Districts. Therefore, content is easier to coordinate. In general, preachers in Jayapura City prefer themes around issues of faith, jurisprudence, and morals. Besides that, the preacher also often chooses content related to events that are currently viral. Meanwhile, content related to religious moderation, including local wisdom, is still very minimal. Khatib tends to choose a religious theme or context that is safe from controversy because in Jayapura the majority is Christian. In addition, the preachers' and community's literacy is still lacking towards moderation material on religion and local wisdom. The control efforts undertaken by the Ministry of Religion over the implementation of the Friday sermon schedule in Jayapura City need to be increased by capturing all mosques. There needs to be a mapping related to the distribution of preachers, da'wah themes, the religious characteristics of community groups as objects of da'wah so that the preaching delivered does not impress provocative da'wah just because it differs in religious understanding.